A biomaterial with a channel-like pore architecture induces endochondral healing of bone defects. Issue 1 (December 2018) - Petersen, A.; Princ, A.; Korus, G.; Ellinghaus, A.; Leemhuis, H.; Herrera, A.; Klaumünzer, A.; Schreivogel, S.; Woloszyk, A.; Schmidt-Bleek, K.; Geissler, S.; Heschel, I.; et al.
Abstract Biomaterials developed to treat bone defects have classically focused on bone healing via direct, intramembranous ossification. In contrast, most bones in our body develop from a cartilage template via a second pathway called endochondral ossification. The unsolved clinical challenge to regenerate large bone defects has brought endochondral ossification into discussion as an alternative approach for bone healing. However, a biomaterial strategy for the regeneration of large bone defects via endochondral ossification is missing. Here we report on a biomaterial with a channel-like pore architecture to control cell recruitment and tissue patterning in the early phase of healing. In consequence of extracellular matrix alignment, CD146+ progenitor cell accumulation and restrained vascularization, a highly organized endochondral ossification process is induced in rats. Our findings demonstrate that a pure biomaterial approach has the potential to recapitulate a developmental bone growth process for bone healing. This might motivate future strategies for biomaterial-based tissue regeneration. A bioengineering approach to enhance the regeneration of large bone defects is lacking. Here, the authors show that a biomaterial scaffold with a channel-like pore architecture enables organized endochondral ossification through directional cell recruitment and extracellular matrix alignment.